Are Mergers and Acquisitions Necessarily Anti-competitive? Empirical Evidence from India's Manufacturing Sector. (August 2018) - Mishra, Pulak
Policy initiatives and regulatory changes made during the last two-and-half decades of economic reforms have led to a considerable increase in the number of mergers and acquisitions (M&As) in the Indian corporate sector. Given the policy-induced flexibilities, while the domestic firms have taken the route of mergers to restructure their business and grow, the foreign firms have preferred to enter into specific markets through acquisitions and raise monopoly power therein. In this context, the present article attempts to examine the impact of M&As on market the structure in major industries of the Indian manufacturing sector during the post-reform period. Using a panel dataset of 34 major industries for the period 2001–2009, the article finds that M&As do not necessarily cause any appreciable adverse impact on market concentration. Instead, the degrees of sellers' concentration are influenced by the growth of market, capital intensity, firms' advertising efforts and their financial performance. The findings of the present article, therefore, suggest for a rethink on policies and regulations relating to M&A, international trade and intellectual property, as they play a significant role in enhancing firms' competitiveness and restricting the emergence of a monopolistic power. JEL Classification: L1, L4, L5, O3